The Responsibilities of Father and Son Towards Their Families As Seen in Mario Puzo’s The Godfather - Astuti, Amelia Yuli; Gaho, Indrayanti (Jurnal Ilmiah Langue and Parole, 2025)
The title of this research is The Responsibilities of Father and Son Towards Their Families as seen in Mario Puzo’s The Godfather. This research problem focuses on the differences and similarities between the main characters of father and son, as well as the background of the attitude changes experienced by Michael Corleone as reflected in the novel The Godfather. This research is a qualitative descriptive research. By quoting sentences or words that show personality characteristics and then describing them. The results of this research show that the personality structure in Freud’s Psychoanalysis theory (1923) shows that the personalities of Vito and Michael are influenced by Id, Ego, and Superego. This happens due to the different lives of Vito and Michael who have different personalities in the world of mafia families. Michael’s character change was caused by the deep trauma when his father, Don Vito Corleone, was shot by the enemies. Research on psychoanalysis is essential to understanding this research as it can provide deeper insights into the motivations, behaviors, and relationships of the characters reflected in The Godfather. Psychoanalysis can help in analyzing family dynamics, themes of morality and violence, and provide a new perspective overall. Based on the analysis of the main character through psychoanalysis research, it can be concluded that the main character experiences many events that cause psychological turmoil because of the life they live as part of a mafia family.